An autonomous lab on a chip for space flight calibration of gravity-induced transcellular calcium polarization in single-cell fern spores - Park, J.H.; Salmi, Mari L.; Wan Salim, Wan Wardatul Amani; Rademacher, A.T.; Wickizer, B.; Schooley, Aaron; Benton, J.E.; Cantero, A.; Argote, P.; Ren, M.; Zhang, Min; Porterfield, David Marshall; et al. (Royal Society of Chemistry, 2017)
This report describes the development of lab-on-a-chip device designed to measure changes in cellular ion gradients that are induced by changes in gravitational (g) forces. The bioCD presented here detects differential calcium ion concentrations outside of individual cells. The device includes sufficient replicates for statistical analysis of the gradients around multiple single cells and around control wells that are empty or include dead cells. In the data presented, the degree of the cellular response correlates with the magnitude of the g-force applied via rotation of the bioCD. The experiments recorded the longest continuous observation of a cellular response to hypergravity made to date, and they demonstrate the potential utility of this device for assaying the threshold of cells' g-force responses in spaceflight conditions.